2021
DOI: 10.1073/pnas.2107179118
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence to understand the human factor for effective rapid testing against SARS-CoV-2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) rapid antigen point-of-care and home tests are available to laypeople. In four cross-sectional mixed-methods data collections conducted between December 2020 and March 2021 (n = 4,026), we showed that a majority of subjects were willing to test despite mistrust and ignorance regarding rapid tests’ validity. Experimental evidence shows that low costs and access to events could increase testing intentions. Mandatory reporting and isolation after positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
0
12
1
3
Order By: Relevance
“…Compared with our data, recent studies demonstrated that people in European countries had a higher intention (from 72% to 79%) to use SARS‐CoV‐2 RAST. 9 , 26 , 27 This discrepancy may be attributed to several reasons. First, the current SARS‐CoV‐2 RAST kits usually require nasal swabs sampling, while the majority of NAATs conducted in China are sampled from throat swabs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with our data, recent studies demonstrated that people in European countries had a higher intention (from 72% to 79%) to use SARS‐CoV‐2 RAST. 9 , 26 , 27 This discrepancy may be attributed to several reasons. First, the current SARS‐CoV‐2 RAST kits usually require nasal swabs sampling, while the majority of NAATs conducted in China are sampled from throat swabs.…”
Section: Discussionmentioning
confidence: 99%
“…To promote the acceptance of SARS‐CoV‐2 RAST, a key issue should be clarified regarding people's attitudes toward SARS‐CoV‐2 RAST. 9 In China, large‐scale NATT has achieved great success and is still the dominant measure with high acceptance for SARS‐CoV‐2 screening in public. However, little is known about the influencing factors for accepting SARS‐CoV‐2 RAST.…”
Section: Introductionmentioning
confidence: 99%
“…An increased use imposes the significant risk that false-negative results will suggest to POCT-Ag negative asymptomatic probands (travelers) that hygienic safety measures, such as social distancing, medical masks, and frequent air exchange, are less necessary [19]. Institutional Review Board Statement: Ethical review and approval were waived for this study because we employed approved CE labeled standard laboratory tests on samples obtained for performing these tests.…”
Section: Discussionmentioning
confidence: 99%
“…Viele Testmöglichkeiten sind dabei relativ schnell, recht weit verbreitet und teilweise preiswert oder kostenlos. Entsprechenden Testangeboten wird ein großes Potential in der Bekämpfung der Pandemie zugeschrieben [5,6]. Die Bedeutung von entsprechenden Schnelltests wird beispielsweise von Mina et al akzentuiert [7].…”
Section: Introductionunclassified
“…Die Bereitschaft zur Durchführung von Schnelltests wurde im weiteren Verlauf (von Dezember 2020 bis März 2021) wiederholt als hoch klassifiziert [5]. Die Wahrscheinlichkeit der Inanspruchnahme war beispielsweise positiv mit einem niedrigen Preis und einer einfachen Anwendung assoziiert [5].…”
Section: Introductionunclassified